Pretreatment with MK-801 or the Lazaroid U-83836E does not Enhance Striatal Graft Survival - Ulrika Mundt-Petersen; Jenny Karlsson; Gabriele S. Kaminski Schierle; Patrik Brundin (Cell Transplantation, 2000)
A large proportion of grafted striatal neurons die, and mechanisms by which they succumb may involve excitotoxicity and oxidative stress. We investigated the effects of pretreatment of the graft tissue with the N-methyl-D-aspartate (NMDA) receptor antagonist (+)dizocilpine hydrogen maleate (MK-801) and lipid peroxidation inhibitor lazaroid U-83836E on the survival of transplanted striatal neurons. Neither compound increased the survival of grafts, suggesting that NMDA-related excitotoxicity or oxidative stress may not be primary mediators of cell death in striatal grafts.